The Extent of Sustainable Accounting Implementation and Identification of Factors Affecting Sustainable Accounting in the ‎Saudi Business Environment (Case Study: SMEs in the Asir Region)‎ - Alhaj , Abeer Bakri Siralkhatim; Alamer, Mohammed Dhafer K.; Mostafa , Engy Ahmed Abdel Ghany (International Journal of Accounting and Economics Studies, 2025)
The main purpose of this study was The Extent of Sustainable Accounting Implementation and Identification of Factors Affecting Sustaina-‎ble Accounting in The Saudi Business Environment (Case Study: SMEs in the Asir Region). The method of this study was Descriptive – ‎survey. The statistical population of this study was SMEs managers in Asir Region that their number is 100 persons. The sample size was ‎estimated using Cochran formulate as 80 mangers and they were selected by random cluster sampling. The tool to collect data was a re-‎searcher-made questionnaire was used. The validity of the questionnaire was confirmed by supervisor and a number of management and ‎accounting professors and the reliability of the questionnaire was confirmed by Cranach Alpha which was 0.92. The collected question-‎naires were analyzed by One-sample T-test, Exploratory factor analysis (EFA) and AHP Fuzzy by SPSS and Matlab software. Findings ‎showed the rate of using sustainable accounting in the Saudi business environment is significantly at the desired level and above the ex-‎pected average level. Also, findings showed that factors affecting sustainable accounting were identified and categorized into five main ‎factors including ownership structure, company size, financial leverage, corporate governance structure, and supervisory structure‎.
Keywords: Sustainable Accounting; SMEs; Asir